LOKAKARYA PENYUSUNAN MODUL PROJEK PENGUATAN PROFIL PELAJAR PANCASILA BAGI GURU KOMITE PEMBELAJARAN SDIT ANNAJIAH LUBUKLINGGAU - Yaspin Yolanda; Andriana Sofiarini; Candres Abadi (LP4MK STKIP PGRI Lubuklinggau, 2023)
This activity was held on August 12-13, 2023 involving school facilitators batch 1. The aim of this lokakarya was to strengthen understanding of the implementation of the Pancasila student profile strengthening project (P5) and design ideas for modifying project modules that are in accordance with the context of the situation and needs of the school. Activities using the